A subcultura gótica no audiovisual: uma análise dos videoclipes da banda Bauhaus - HADDAD, Suzana Taleb (2017)
This research proposes analyzes of audiovisual pieces - video clips, television commercials and feature films - starring by the british band Bauhaus and /or by his singer Peter Murphy between 1979 and 1983: video clips Telegram Sam, Mask, Spirit and Ziggy Stardust, the television commercials Maxell Tape 1 and Maxell Tape 2, and the opening part of the movie Fome de Viver. In our analyzes, we seek to relate the characteristics of these pieces to the aesthetic project of the band, linked to the gothic subculture, and also to understand how this project was absorbed and diluted by advertising and products of great visibility in the cultural industry, as well as the contact with these products interfered in the aesthetics of the band's music videos that came later, during the short but successful career of the Bauhaus.